2014
DOI: 10.4028/www.scientific.net/amm.519-520.1581
|View full text |Cite
|
Sign up to set email alerts
|

Study of Patient Waiting Time in the Emergence Department: An Example of a Medical Center in New Taipei County, Taiwan

Abstract: explain the higher incidence of GPLA in individuals with diabetes mellitus. 7 Gas-forming PLA is a significant cause of morbidity and mortality, especially in older adults with diabetes mellitus. To reduce morbidity and mortality, adequate antibiotics, such as ceftriaxone with or without metronidazole, and good control of blood glucose with early adequate drainage are mandatory. Surgery should not be delayed if medical treatment or percutaneous drainage fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous research on waiting times have focused on analysing different waiting situations, reducing waiting time or improving waiting conditions (Durrande-Moreau and Usunier 1999;Nie 2000;Bournes and Mitchell 2002;Kutash and Northrop 2007;Minton 2008;Norman 2008;Zhou and Soman 2008;Ho et al 2014;Asthana et al 2015;Frank et al 2015). The goal is to avoid letting waiting time negatively influence the perception of service providing people.…”
Section: Waiting Situations and The Possibility For Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on waiting times have focused on analysing different waiting situations, reducing waiting time or improving waiting conditions (Durrande-Moreau and Usunier 1999;Nie 2000;Bournes and Mitchell 2002;Kutash and Northrop 2007;Minton 2008;Norman 2008;Zhou and Soman 2008;Ho et al 2014;Asthana et al 2015;Frank et al 2015). The goal is to avoid letting waiting time negatively influence the perception of service providing people.…”
Section: Waiting Situations and The Possibility For Communicationmentioning
confidence: 99%
“…Therefore, researchers analyse waiting conditions and derive implications for service providers, for example, to inform customers about the effective waiting time (Nie 2000) or to arrange fair conditions in waiting lines (Norman 2008;Zhou and Soman 2008). Other studies deal with waiting in critical situations like waiting for relatives in hospitals (Bournes and Mitchell 2002;Kutash and Northrop 2007;Ho et al 2014). Kutash and Northrop (2007) found that family members can find emotional support in the waiting room by talking to other waiting individuals.…”
Section: Waiting Situations and The Possibility For Communicationmentioning
confidence: 99%